Comparative pharmacokinetics of six coumarins in normal and breast cancer bone-metastatic mice after oral administration of Wenshen Zhuanggu Formula. (5th October 2018) - Chen, Weiling; Li, Jiajia; Sun, Zhenping; Wu, Chunyu; Ma, Jiao; Wang, Jianyi; Liu, Sheng; Han, Xianghui
Abstract: Ethnopharmacological relevance: Wenshen Zhuanggu Formula (WSZG) is a traditional Chinese medicine (TCM) prescription used in clinics for adjuvant treatment of breast cancer bone metastases in Longhua Hospital in China. WSZG has been reported to decrease the risk of bone metastases and alleviate the severity of bone lesions in a breast cancer xenograft model. Aim of the study: The present study aimed at investigating the pharmacokinetic behaviors of six coumarins in normal and breast cancer bone-metastatic mice following oral administration of WSZG extract. Materials and methods: A bone-metastatic mouse model was established by intracardiac injection of MDA-MB-231BO breast cancer cells, and WSZG extract (1.60 g/kg) was given orally to the model and normal mice for 4 weeks. Then, the blood pharmacokinetic parameters of six bioactive components from WSZG (psoralen, isopsoralen, bergapten, xanthotoxin, osthole, and imperatorin) were analyzed by liquid chromatography tandem mass spectrometry. Results: There were significant differences in pharmacokinetic behaviors between normal and pathological states. Compared with normal mice, the model mice showed significantly increased AUC 0–t and AUC 0–∞ of the bioactive compounds ( P  < 0.05) and significantly decreased total blood clearance ( CL Z /F ) ( P  < 0.05). Conclusions: The different pharmacokinetic behaviors might be partly ascribed to intestinal functional disorders and imbalance of gastrointestinal microbiota under the morbid state. The findings provide some valuable information to evaluate the clinical efficacy and safety of this TCM formula. Graphical abstract: fx1